PENGARUH AKUNTABILITAS, TRANSPARANSI DAN PENGAWASAN TERHADAP KINERJA PEMERINTAH KABUPATEN MAGETAN - Herry Purnomo; Niken Eri Wahyuni; Hery Hermawan (Universitas Merdeka Madiun, 2025)
Since Government Regulation Number 8 of 2006 concerning Financial Reporting and Performance of Government Agencies. In this Government Regulation itself, the performance measurement system for the government, both central and regional, begins to be regulated. Public accountability and public transparency are the most important principles for realizing good regional government performance. Basically, supervision is completely directed at avoiding the possibility of deviation or deviation from the goals to be achieved. Through supervision, it is hoped that it can help implement the policies that have been set to achieve the planned goals effectively and efficiently. The aim of the research is to determine the influence of accountability, transparency and supervision on the performance of Magetan Regency. This type of research is quantitative research. Data collection techniques use questionnaires and documentation. The analysis technique uses multiple linear regression, hypothesis testing (t test and F test). The results obtained show that (1) There is an influence of accountability on the performance of the Magetan Regency government. (2) There is an influence of transparency on the performance of the Magetan Regency government. (3) There is an influence of supervision on the performance of the Magetan Regency government. (4) There is an influence of accountability, transparency and supervision on the performance of the Magetan Regency government. (5) The coefficient of determination (R Square) obtained is 0.743. This means that variations and the three independent variables, namely accountability, transparency and supervision, contribute to Regency Government Performance by 74.3%, while the other 25.7% can be explained by other variables not included in the research.